The Effectiveness of Acupuncture at PC6, HT7, GV20, and Ear Shenmen on Blood Pressure Reduction - Pihir Kassor; Jatmiko Rinto Wahyudi; Hanung Presetya (HAKTI : Indonesian Acupuncture Therapists Association, 2026)
Hypertension is a chronic disease that requires long- term management, in which complementary therapies such as acupuncture and herbal medicine are increasingly used to support blood pressure control. This quasi-experimental study aimed to compare the effectiveness of acupuncture at PC6, HT7, GV20, and Ear Shenmen points with Orthosiphon stamineus herbal therapy among 30 patients with hypertension using a two-group pretest–posttest design over four weeks. The results showed that both interventions significantly reduced systolic and diastolic blood pressure (p < 0.050), indicating that acupuncture and Orthosiphon stamineus are effective complementary therapies for patients with mild to moderate hypertension